2021
DOI: 10.3866/pku.whxb202111021
|View full text |Cite
|
Sign up to set email alerts
|

Hollow NiCo<sub>2</sub>S<sub>4</sub> Nanospheres as a Cocatalyst to Support ZnIn<sub>2</sub>S<sub>4</sub> Nanosheets for Visible-Light-Driven Hydrogen Production

Abstract: The rational interface tailoring of nanosheets on hollow spheres is a promising strategy to develop efficient photocatalysts for hydrogen production with solar energy. Among the various photocatalyst materials, metal sulfides have been extensively researched because of their relatively narrow band gap and superior visible-light response. ZnIn2S4 is a layered ternary chalcogenide semiconductor photocatalyst with a tunable band gap energy (approximately 2.4 eV). Among various metal sulfide photocatalysts, ZnIn2S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 64 publications
2
47
0
Order By: Relevance
“…49 Thus, it was concluded that the g-C 3 N 4 /CoP@C-200 composite material had a strong charge-separation ability, which led to an improvement in H 2 production performance. [50][51][52][53][54] This conclusion was consistent with the results obtained from the EIS analysis; the Nyquist plot of the composite had the smallest semicircle diameter by comparison with those of g-C 3 N 4 and CoP@C (Fig. 4d).…”
Section: Crystengcomm Papersupporting
confidence: 89%
“…49 Thus, it was concluded that the g-C 3 N 4 /CoP@C-200 composite material had a strong charge-separation ability, which led to an improvement in H 2 production performance. [50][51][52][53][54] This conclusion was consistent with the results obtained from the EIS analysis; the Nyquist plot of the composite had the smallest semicircle diameter by comparison with those of g-C 3 N 4 and CoP@C (Fig. 4d).…”
Section: Crystengcomm Papersupporting
confidence: 89%
“…Generally, a larger arc radius corresponds to a greater inherent resistance. [77][78][79][80][81][82][83] Excitingly, 10CN/BWO shows the smallest arc radius among the samples, showing that 10CN/BWO has the lowest charge-transfer resistance, greatly boosting its efficient charge separation.…”
Section: Photocatalytic Enhancement Mechanismmentioning
confidence: 99%
“…In order to investigate the photocatalytic mechanism, UPS was performed (Fig. 8a and b), and the W f (work function), E V and E C can be estimated based on the following equations: 54,55 W f = 21.22 − E 1 E V = W f + E 2 E C = E V − E g E NHE = − E AVS − 4.5where E 1 is the upper emission onset energy, E 2 is the lower emission onset energy, E NHE is the energy of the normal hydrogen electrode and E AVS is the energy of absolute vacuum. The E V and E C values of the Cd 0.5 Zn 0.5 S are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…52,53 In order to investigate the photocatalytic mechanism, UPS was performed (Fig. 8a and b), and the W f (work function), E V and E C can be estimated based on the following equations: 54,55 W f = 21.22 À E 1…”
Section: Photocatalytic Mechanism Of Nis/cd 05 Zn 05 S Nanocompositesmentioning
confidence: 99%